2015
DOI: 10.1093/carcin/bgv172
|View full text |Cite
|
Sign up to set email alerts
|

Alternatively spliced isoforms of IL-32 differentially influence cell death pathways in cancer cell lines

Abstract: Alternative splicing is a biological mechanism that enables the synthesis of several isoforms with different or even opposite functions. This process must be tightly regulated to prevent unwanted isoform expression favoring pathological processes. Some isoforms of interleukin 32 (IL-32) are reported to be more potent in inducing inflammation, however the role in cell death remains to be investigated. This study demonstrates that IL-32γ and IL-32β can induce caspase-8-dependent cell death whereas this was not o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 48 publications
6
56
0
Order By: Relevance
“…One of the most noteworthy observations is that IL-32 is still not found in rodents, such as mice and rats. Recent discoveries in this area confirmed earlier hypothesis -alternative splicing can be a mighty regulator of isoform types which are produced in various conditions and tissue types (18).…”
Section: Isoformssupporting
confidence: 62%
See 4 more Smart Citations
“…One of the most noteworthy observations is that IL-32 is still not found in rodents, such as mice and rats. Recent discoveries in this area confirmed earlier hypothesis -alternative splicing can be a mighty regulator of isoform types which are produced in various conditions and tissue types (18).…”
Section: Isoformssupporting
confidence: 62%
“…IL-32θ inhibited epithelial-mesenchymal transition (EMT), resulting in the suppression of migratory and invasive capabilities of HT29 colon cancer cells (74). Higher levels of IL-32 were reported in many other cancers: melanoma, thyroid, renal cell (18,71,75). Recent studies have revealed higher expression of IL-32 in human pancreas, liver, and esophagus cancer tissues, compared with normal tissue or serum (76)(77)(78).…”
Section: Role In Cancer Biologymentioning
confidence: 99%
See 3 more Smart Citations